Penggunaan Aplikasi Elsimil dan Peran Tim Pendamping Keluarga terhadap Kunjungan Peserta KB - Lelyans Surya Risma Sinapa; Yenny Puspitasari; Andi Hayyun Abiddin (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT The Family Planning Program is one of the government's strategic efforts to control population growth and improve the quality of reproductive health. Technological innovation through the Electronic Ready for Marriage and Pregnancy (Elsimil) application and assistance by the Family Assistance Team is expected to encourage community participation, including increasing visits by family planning participants. This study aims to analyze the effect of the use of the Elsimil application and the role of the Family Planning Team on the number of family planning participant visits. This study is an observational study using a cross-sectional approach with a population of all fertile-age couples at the Tokorondo Community Health Center totaling 135 PUS. Purposive sampling technique was used to obtain 102 respondents who met the following inclusion criteria: prospective brides and grooms, PUS who have not used family planning, can read and write and are willing to be research respondents. Meanwhile, couples participating in family planning who are not within the working area of the Tokorondo Community Health Center, couples whose visits are not recorded at the Tokorondo Community Health Center and couples who are not of fertile age are exclusion criteria. Data collection was conducted in December 2024 at the Tokorondo Community Health Center using a questionnaire that asked about the use of the Elsimil application, the role of the Family Support Team, and visits to family planning participants. Data were analyzed using a linear regression test. The results showed that the use of the Elsimil application had a positive and significant effect on visits to family planning participants (α 0.006 0.05) and the role of the Family Support Team had a positive and significant effect on visits to family planning participants (α 0.003 0.05). The local government and the National Population and Family Planning Agency (BKKBN) need to provide ongoing training for TPK members regarding the use of the Elsimil application, effective communication techniques, and family planning IEC materials so that the assistance provided is more comprehensive and targeted. Keywords: Family Planning, Elsimil, Family Assistance Team.   ABSTRAK Program Keluarga Berencana salah satu upaya strategis pemerintah untuk mengendalikan pertumbuhan penduduk dan meningkatkan kualitas kesehatan reproduksi. Inovasi teknologi melalui aplikasi Elektronik Siap Nikah dan Hamil (Elsimil) dan pendampingan oleh Tim Pendamping Keluarga diharapkan dapat mendorong partisipasi masyarakat, termasuk peningkatan kunjungan peserta KB. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan aplikasi Elsimil dan peran TPK terhadap jumlah kunjungan peserta KB. Penelitian  ini  merupakan  penelitian observasional  dengan    menggunakan  pendekatan Cross Sectional dengan populasi seluruh pasangan usia subur yangada di puskesmas Tokorondo sebanyak 135 PUS. Teknik purposive sampling digunakan untuk mendapatkan 102 responden yang memenuhi kriteria inklusi sebagai berikut: calon pengantin, PUS yang belum menggunakan KB, Bisamembaca dan menulis dan bersedia menjadi responden penelitian. Sedangkan  pasangan   peserta   KB   yang   bukan  berada   dalam   wilayah   kerja Puskesmas Tokorondo, pasangan yang kunjungan tidak tercatat di Puskesmas Tokorondo dan pasangan yang tidak masuk dalam usia subur merupakan kriteria eksklusi. Pengumpulan data dilakukan pada bulan Maret 2025 di Puskesmas Tokorondo dengan menggunakan kuesioner yang menanyakan tentang penggunaan aplikasielsimil, Peran Tim Pendamping Keluarga dan kunjungan peserta KB. Data dianalisis dengan menggunakan uji regresi linier. Hasil penelitian menunjukkan bahwa penggunaan aplikasi Elsimil secara positif dan signifikan berpengaruh terhadap kunjungan peserta KB (α 0.006 0.05) dan peran Tim Pendamping Keluarga secara positif dan signifikan berpengaruh terhadap kunjungan peserta KB (α 0.003 0.05). Pemerintah daerah dan BKKBN perlu memberikan pelatihan berkelanjutan bagi anggota TPK terkait pemanfaatan aplikasi Elsimil, teknik komunikasi efektif, dan materi KIE KB agar pendampingan yang diberikan lebih komprehensif dan tepat sasaran. Kata Kunci: Keluarga Berencana, Elsimil, Tim Pendamping Keluarga.